Improving school teachers’ self-efficacy and knowledge on food allergy and management of anaphylaxis using a virtual multidisciplinary workshop - Rubanandhini Nagajothi; Si Hui Goh; Hwee Hoon Lim; Wenyin Loh; Kok Wee Chong (Annals, Academy of Medicine, Singapore)
Children with food allergies are at risk of inadvertent allergic reactions that range from mild to potentially life-threatening anaphylaxis, even with appropriate dietary avoidance.1 This risk is often increased in community settings such as schools via accidental exposure to allergens during learning activities or meal times. A quarter of children were found to have their first allergic reaction on school grounds.2 Studies of self-reported reactions have shown that 16–18% of school-aged children with known food allergy experienced an allergic reaction in school.3 In Singapore, the prevalence of self-reported food allergy among children aged 11–30 months could be as high as 5%. Food allergies can contribute to reduced quality of life and barriers to participation in day-to-day activities.4 Therefore, it is crucial that all schools are prepared to effectively prevent and manage food-related allergic reactions.